Решите 3 и 4 плиз с решением  !

  • 3)
    5b           2a
    ——  —  ——-=
    ax+ay       bx+by

    5b           2a
    ——  —  ——-=
    a(x+y)      b(x+y)

    5b*b              2a*a
    ————  —  ————=
    a(x+y)*b        b(x+y)*a

    5b^2-2a^2    5b^2-2a^2
    —————= —————-
    ab(x+y)           abx+aby

    4)
    3x              6x
    ———  —  ——-=
    4x+4y       8x+8y

    3x                6x
    ———  —  ——-=

    4(x+y)       8(x+y)

    3x*2                6x
    ————  —  ———=

    4(x+y)*2       8(x+y)

    6x-6x
    ———-= 0
    8(x+y)